Compatibility and correlation of multi-attribute decision making: a case of industrial relocation - Martino Neto, Jose [UNESP]; Salomon, Valerio Antonio Pamplona [UNESP]; Ortiz-Barrios, Miguel Angel; Petrillo, Antonella (Springer Nature, 2022)
Industrial relocation (IR) is a business strategy consisting of moving operations locations. The purpose of this paper is to present how to assess, with multi-attribute decision-making (MADM), alternatives for IR. With MADM, IR strategies can be assessed not only based on a single attribute, as costs, or profits. This paper presents the application of MADM in a real case of IR. Four leading methods of MADM were applied: analytic hierarchy process (AHP), multi-attribute utility theory (MAUT), multi-attribute value theory (MAVT), and technique of order preference by similarity to ideal solution (TOPSIS). Results of AHP, MAUT, MAVT, and TOPSIS were quite similar, indicating the decision for the company not to relocate. A joint comparison of results with compatibility indices and correlation coefficients is the major novelty presented by this paper to the field of Operations Research, known as MADM.
Keywords: Analytic hierarchy process; Compatibility; Correlation; Industrial relocation; Multi-attribute utility theory; Technique of order preference by similarity to ideal solution